Characterization of selectively laser melted Ti-6Al-4 V micro-lattice struts - Rafidah, Hasan; Mines, Robert; Fox, Peter (Elsevier BV, 2011)
This paper presents a characterization study of titanium alloy (Ti-6Al-4 V) micro-struts manufactured using selective laser melting (SLM). Previous test results from sandwich structures with titanium alloy micro-lattice cores showed that the material experienced brittle fracture failure, although it had a reasonable specific strength. Therefore, the microstructure present in the struts has been investigated in order to understand its influence on the mechanical behaviour. Conclusions on the way forward for improved mechanical behaviour, by the use of subsequent heat treatment and careful control of the manufacturing process can then be identified.